Incentivo apopularização da robótica educacional como recurso de ensino por meio da utilização de um sistema de geração automatizada de planos de ensino - Passos, Daniel Deyson Nunes (2021)
Teaching Mathematics content in Elementary II presents some challenges, many of which are being overcome with the use of information and communication technologies. In this context, Educational Robotics has been gaining space, being increasingly present in school environments. However, there is a scarcity of materials to help teachers use Educational Robotics in the classroom. To start overcoming this difficulty, we present the development of a lesson plan generation system using an ontology capable of helping the teaching and learning of mathematics using Educational Robotics. The ontology named Ontology of Educational Robotics Teaching and Learning (Onto-ENSINARE) was built based on the Ontology Development 101 methodology with the aspects of completeness, consistency and conciseness. In verifying the ontology, SPARQL Protocol and RDF Query Language (SPARQL) queries were used to obtain useful answers for elementary II mathematics teachers. From the ontology, the System for Integrated Lesson Plan Generation for Robotic Education (SCIENCE) was built and tested by 11 mathematics teachers. The teachers who tested the system work in municipal and state schools located in the cities of Mossoró and Nova Cruz, in Rio Grande do Norte, and in the cities of Piancó, Rio Tinto, Mamanguape and Sapé, in Paraíba. Due to the covid-19 pandemic, the test did not involve using the system in the classroom. To validate the system, pre-test and post-test questionnaires were developed. The pre-test questionnaire aims to identify information about the participants' knowledge of mathematics, educational robotics, and information technology. The post-test questionnaire, besides seeking to observe possible changes in the testers' thinking after using the system, also aims to perform its validation according to the Technology Acceptance Model (TAM) methodology. The results obtained in the validation showed a good acceptance, in which 81.8% of the teachers showed great interest in using the system in their mathematics classes. The search requirements of the lesson plans of the Mathematics subject with the support of Educational Robotics were considered useful for use in the classroom